Non-compliant left atrium masquerading as severe mitral regurgitation on cardiac catheterisation haemodynamics - Mkoko, Philasande; Cupido, Blanche (SA Heart Journal, 2020)
A prominent v wave on a capillary wedge or left atrial pressure tracings classically signify significant mitral regurgitation. However, infiltrative disease involving the left atrium and left atrial scar from prior catheter ablation or Maze procedures, may produce a similar waveform due to noncompliance of the left atrium.